Life histories of Paucispinigera Freeman, Paraborniella Freeman and Paratendipes Kieffer (Diptera: Chironomidae) with phylogenetic considerations - Cranston, Peter S. (Zootaxa, 2020)
The immature stages of the New Zealand endemic Paucispinigera Freeman and Paraborniella Freeman, endemic to Australia, are described fully for the first time. A new species of Paratendipes Kieffer endemic to Australia is described in all life stages. Morphological support from larvae for placement in a ‘Microtendipes’ group in tribe Chironomini includes the 6-segmented antenna with Lauterborn organs on the 2nd and 3rd segments, and a well-demarcated, multi-toothed ventromentum. The pupa has a few-branched thoracic horn and the distribution of taeniate L-setae is informative. Significant differentiating characters of the adult male include the form of tibial apices and the structures of superior and median volsellae in the genitalia. In the wing of Paucispinigera, the squama lacks setae, contrary to the original description, and unusually has vein M1+2 setose in both sexes and also the M3+4 setose in the female. An apical spine on the gonostylus of Paucispinigera is unusual. The female genitalia are described here for the first time but lack phylogenetically informative variation. An Australian species of the widespread genus Paratendipes Kieffer, described here as Paratendipes sinespina sp. n., is provided for comparison. Paucispinigera and Paraborniella each warrant independent generic rank.